Stroke through a lens: Exposing the challenges of establishing a visual arts project as a research engagement activity. (1st January 2017) - Cook, Jenny; Fudge, Nina; Stevens, Eleanor; McKevitt, Christopher
Abstract : To celebrate 20 years of an epidemiological study, the South London Stroke Register, we collaborated with student artists and stroke survivors to create an exhibition of visual arts displayed at a series of events in 2015–16. This paper explores the expectations placed on researchers to engage with different publics, touching on current debates around institutional support and recognition. We critically reflect on the project process, identifying challenges and offering recommendations. We include the perspectives of the stroke survivors and the student artists, and examples of the artwork.